2016
DOI: 10.1515/jbcr-2016-0004
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis of the Forensic Autopsies, Performed in the Department of Forensic Medicine of University Hospital Pleven for the Period 2009-2013 (A Preliminary Report)

Abstract: Summary The study is a statistical analysis of the dynamics and structure of forensic autopsies performed on dead bodies and body remains at University Hospital “Dr. Georgi Stranski” in Pleven. The study was based on forensic autopsy records database and forensic autopsy reports for the period 2009-2013. A total of 976 cases, including forensic autopsies, exhumations, examination of bone remains and inspection of dead bodies at the site of death (without following forensic autopsy), were analyzed. The stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…These were not similar to our study. 4 In a similar study done on mothers, analysis of the data of autopsies done to find the cause of maternal deaths showed that the cause of death was determined after autopsy and it was compatible with clinical diagnosis in around 60% cases, only. In our study we couldn't find data regarding the clinical diagnosis and clinical etiology cause of death.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…These were not similar to our study. 4 In a similar study done on mothers, analysis of the data of autopsies done to find the cause of maternal deaths showed that the cause of death was determined after autopsy and it was compatible with clinical diagnosis in around 60% cases, only. In our study we couldn't find data regarding the clinical diagnosis and clinical etiology cause of death.…”
Section: Discussionmentioning
confidence: 93%
“…Major factor behind all the cases of autopsy is 'economic crises', which is the leading cause of all crimes in our society. 3,4 Young offenders are becoming increasingly violent and this is a cause for concern, as they are future generation. 2 Studies have shown that cause of death revealed after autopsies was cardiovascular and cerebrovascular lesion in around 40% and 20% among all, respectively; and in more than 30% of cases, declared cause of death before autopsy was wrong.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Young offenders are becoming increasingly violent and this is a cause for concern, as they are future of any nation 2 . Literature review showed that in many studies, cause of death revealed after autopsies were cardiovascular and cerebrovascular lesion in around 40% and 20% among all, respectively; and in more than 30% of cases, wrong declaration regarding cause of death before autopsy was made 5,6 .…”
Section: Introductionmentioning
confidence: 99%